1990
DOI: 10.1080/00049158.1990.10676059
|View full text |Cite
|
Sign up to set email alerts
|

Sequential sampling and modelling for mean dominant height estimation

Abstract: A method of checking the validity of model predictions of the mean dominant height {MDH) for a cutting unit using sequential sampling is presented. Inventory data provided by the New South Wales Forestry Commission were used to test the impact of decision criteria and acceptable type I and type 2 error levels on average sample size. Using sequential sampling to check model predictions of cutting unit MDH lowered the standard error of the prediction and reduced the maximum error by over half that of the using m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…the predictions are significantly different or not usefully close to the ESV found at the sample point) would quickly indicate that the public forest model is inadequate and should not be used in privately managed forests. Brack and Marshall ( 1990) concluded that, depending on the error levels acceptable to the user, as few as three sample points could accept or reject a model as useful. If the test proves that the model is inadequate, the proposed approach allows the sample data to be reused to help determine an unbiased estimate of the new population without recourse to the invalidated model.…”
Section: Discussionmentioning
confidence: 98%
“…the predictions are significantly different or not usefully close to the ESV found at the sample point) would quickly indicate that the public forest model is inadequate and should not be used in privately managed forests. Brack and Marshall ( 1990) concluded that, depending on the error levels acceptable to the user, as few as three sample points could accept or reject a model as useful. If the test proves that the model is inadequate, the proposed approach allows the sample data to be reused to help determine an unbiased estimate of the new population without recourse to the invalidated model.…”
Section: Discussionmentioning
confidence: 98%